PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN PENEMUAN (DISCOVERY LEARNING) PADA MATERI PERSAMAAN LINEAR SATU VARIABEL KELAS 7D SMP NEGERI 8 KOTA BOGOR - C. Rubae'ah (Universitas Pakuan, 2021)
IMPROVING STUDENT LEARNING OUTCOMES THROUGH DISCOVERY LEARNING MODELS ON ONE VARIABLE LINEAR EQUATION MATERIALS IN JUNIOR HIGH SCHOOLS (SMP NEGERI 8 KOTA BOGOR)Learning outcomes and students' understanding of the concept of One Variable Equation in Junior High School (SMP Negeri 8 Kota Bogor). is still low. For this reason, it is necessary to apply learning models which are the main contributors that need to be considered in order to improve student learning outcomes. The research was carried out in junior high schools (SMP Negeri 8 Kota Bogor) and aimed to (1) improve student learning outcomes, (2) find out whether Discovery Learning is the right learning model for Mathematics Subjects with Single Variable Linear Equations, (3) determine the magnitude of the increase in student learning outcomes , which is measured as the percentage of the number of students who get a score of 76 or meet the minimum standard of completeness criteria. The results showed that using the Discovery Learning model could significantly improve student learning outcomes in junior high schools (SMP Negeri 8 Kota Bogor). Student learning outcomes increased after using the Discovery Learning model to 70.59% in the first cycle and 100% in the second cycle. The application of this Learning Model makes learning materials more interesting and the classroom atmosphere more pleasant for students, and in the end can increase students' understanding of the material and students' values in evaluation. Therefore, the researcher recommends the use of the Discovery Learning model in learning Mathematics in schools within the Bogor City Education Office.